A Radical Critique of the Learning Outcomes Assessment Movement - Bennett, Michael; Brady, Jacqueline (Radical Teacher, 2014)
The Learning Outcomes Assessment (LOA) movement seems rather innocuous.  Teachers and administrators at colleges and universities are asked to articulate the goals, objectives, measures, and outcomes of the educational process at every level:  from the classroom to the department to the institution as a whole.  Educators engage in this process with the help of curriculum mapping or educational matrices or a host of other tools and templates provided by any number of readily available frameworks (see the website of the National Institute for Learning Outcomes Assessment for many examples).  The information gathered is then used to evaluate curricula, programs, instructors, and institutions for purposes of internal review and external evaluation.